ANALYTICAL PROCEDURES APPLICATION IN AUDITING IFRS REPORTING - Karpachova, О. (Socio-economic relations in the digital society, 2021)
The purpose of the article is to study the practical application of analytical procedures in the audit of IFRS reporting of enterprises. The relevance of the application of analytical procedures in the audit of financial statements in accordance with IFRS has been studied. The main sources of information for analytical procedures are formed. Methods of analytical procedures are analyzed. It is established that the application of analytical procedures is necessary at the end of the audit. Performed as a general review of the financial statements at the end of the audit to assess whether they meet the auditor’s understanding of the entity. That is, the analytical procedures in the final stage are necessary for the auditor to make a final assessment of material misstatements and to help the auditor perform a general «objective view» of the financial statements. An important factor in performing analytical procedures at the end of the audit is that during the audit the auditor provides guidance to management on correcting errors and distortions in the financial statements. Therefore, if management corrects these errors, the financial statements will be different, ie have the correct financial information. It is proved that the analytical procedures at the end of the audit help to assess the statement of management staff on the ability to operate their business on a continuous basis. The use of analytical procedures in planning helps the audit to understand the internal and external environment of the enterprise, assess previous risks, determine the financial statements for the audit approach, plan the budget and the amount of resources needed for the audit. The use of analytical procedures in performing the audit helps the auditor to gather sound evidence. They can be used both in addition to detail tests and as separate analytical procedures on the merits. The purpose of performing analytical procedures at the end of the audit is to summarize the conclusions formed during the audit of financial statements in accordance with IFRS.
Keywords: audit; analytical procedures,; ISA; IFRS; performance of audit; audit procedures; audit of IFRS reporting